El vicio motivacional de incoherencia aplicable a los autos de prisión preventiva del delito de porte no autorizado de armas. - Luguaña Zambonino, Robert Rene (2025)
Based on the figures published by the Judiciary Council on its website, a gradual increase in cases related to the crime of possession and carrying of firearms has been observed since 2018. This phenomenon is linked to the wave of violence currently affecting Ecuador. When discussing the limitation of the right to liberty, the motivation of judges in rulings ordering pretrial detention for the offense of possession and carrying of firearms was analyzed, considering the possible presence of apparent motivational deficiencies, specifically the motivational flaw of incoherence within these rulings. For the development of this research, a qualitative methodology with a descriptive level was employed. General methods such as Documentary Analysis and Case Analysis were used, along with specific methods including inductive and deductive approaches, and legal research methods such as Analytical-Synthetic and Exegetical methods.